Third party audits of the psychosocial work environment in occupational health and safety management systems. (November 2018) - Hohnen, Pernille; Hasle, Peter
Highlights: Psychosocial risks in certified OHSM systems. Psychosocial risks as part of a value chain of regulation. Limited attention to psychosocial risks by The accreditation body. External audit reports do not cover psychosocial work environment issues. The strongest instrument (non-conformity) is not utilised. Explicit attention to psychosocial work environment is needed. Abstract: Occupational health and safety management (OHSM) systems certified according to OHSAS 18, 001 are gaining importance. A key element in OHSAS 18, 001 is third party audits. Psychosocial risks are only briefly mentioned in the standard, and the question therefore remains whether audits in practice cover these risks to a sufficient extent. The article provides a first answer to this question through a study of the whole value chain from accreditation of certification bureaus to the subsequent audits and workplace reactions. The results indicate that the accreditation body pays limited attention to psychosocial risks. Furthermore, auditors are often uncertain as to how they should handle such risks. As a consequence, although auditors may pin point psychosocial work environment issues, auditing practices do not ensure a consistent and encompassing coverage of these issues in their audit reports. Of particular concern is the fact that the strongest instrument (non-conformity) is not utilised at all when auditing psychosocial work environment issues. In sum, the results call for stronger inclusion of the psychosocial work environment in the standard as well as in the accreditation and audit processes.